Design and Implementation of a Web-based Leather Goods Inventory System using the SCM approachased Astina - Zulfikar Abdi; Dewi Maharani; Ricki Ananda (Sistemasi: Jurnal Sistem Informasi, 2023)
UD. Astina is one of the small and medium enterprises (SMEs) engaged in the production of leather goods such as shoes and sandals. The problems that occur at UD. Astina, that is, there is often a shortage and accumulation of supporting materials which are sometimes unstable. UD. Astina still carries out a transaction system manually and has not been computerized so that it hampers the marketing process for the production of leather goods and slows down the attractiveness of customers at UD. Astina. This research aims to design a system at UD. Astina who assists in optimizing the supply process for leather raw materials that must be available when carrying out production by applying the SCM method.The results of research with the construction of Electronic Supply Chain Management (E-SCM) in managing raw materials at UD. Astina can help make UD work easier. Astina in placing orders with suppliers so that they can anticipate shortages of leather raw material stock. So it can be concluded that Electronic Supply Chain Management (E-SCM) can be applied at UD. Astina in the management of leather raw material supplies.